2021
DOI: 10.1111/ans.16600
|View full text |Cite
|
Sign up to set email alerts
|

‘No zone’ approach to the management of stable penetrating neck injuries: a systematic review

Abstract: Background Aim: to review outcomes of the ‘no zone’ approach to penetrating neck injuries (PNIs) with the advent of high‐fidelity computed tomography‐angiography (CT‐A) in order to determine the most appropriate management for stable PNIs. Design: Systematic review. Population: Retrospective and prospective cohort studies of patients who sustained penetrating neck trauma, as defined by an injury which penetrates the platysma, and whose initial management involved CT‐A evaluation. Methods An extensive literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…In this issue of ANZ Journal of Surgery , Chandrananth et al present a review of observational data published between 2006 and 2019. The authors outline the role of CTA in the management of penetrating neck injuries extending beyond platysma 1 . Their results add to the current trend in the published literature supporting a no‐zone approach and advocating for selective interventions and less non‐therapeutic surgical explorations.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…In this issue of ANZ Journal of Surgery , Chandrananth et al present a review of observational data published between 2006 and 2019. The authors outline the role of CTA in the management of penetrating neck injuries extending beyond platysma 1 . Their results add to the current trend in the published literature supporting a no‐zone approach and advocating for selective interventions and less non‐therapeutic surgical explorations.…”
mentioning
confidence: 84%
“…After decades of experience with zone‐based and gradually more selectively practiced surgical management of penetrating neck injuries, a rather radical change is evolving worldwide. Recent literature summarised by Chandrananth et al 1 is proposing to abandon the zone‐based selective management and to rely entirely on multidetector computed tomography (CT) angiography (CTA) in all haemodynamically normal patients with penetrating neck injuries as a guide for operative or non‐operative approach.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Penetrating neck trauma (PNT), defined as full thickness breech of the platysma muscle, account for about 5-10% of all trauma cases, with a mortality of up to 10%. 1 The risk of PNT comes from potential damage to vital vascular and aerodigestive structures. Historically, the risk for vascular and aerodigestive injuries in PNT was categorized based on the entry site of injury based on the 3 anatomical zones of the neck that was first described by Monson et al in 1969.…”
mentioning
confidence: 99%
“…However, later studies demonstrated that the zone approach does not accurately predict injuries. 1 The current practice management guidelines for aerodigestive injuries in PNT from the Western Trauma Association, Eastern Association for the Surgery of Trauma, and World Society for Emergency Surgery vary and either call for multiple overlapping assessments or are dependent on physician discretion. [2][3][4] The tests for aerodigestive injuries include bronchoscopy, esophagoscopy (EGD), and esophagography.…”
mentioning
confidence: 99%